Ontogeny of the spheno‐occipital synchondrosis in a modern Queensland, Australian population using computed tomography. Issue 1 (29th December 2014) - Lottering, Nicolene; MacGregor, Donna M.; Alston, Clair L.; Gregory, Laura S.
ABSTRACT Due to disparity regarding the age at which skeletal maturation of the spheno‐occipital synchondrosis occurs in forensic and biological literature, this study provides recalibrated multislice computed tomography (MSCT) age standards for the Australian (Queensland) population, using a Bayesian statistical approach. The sample comprises retrospective cranial/cervical MSCT scans obtained from 448 males and 416 females aged birth to 20 years from the Skeletal Biology and Forensic Anthropology Research Osteological Database. Fusion status of the synchondrosis was scored using a modified six‐stage scoring tier on an MSCT platform, with negligible observer error (κ = 0.911 ± 0.04, intraclass correlation coefficient = 0.994). Bayesian transition analysis indicates that females are most likely to transition to complete fusion at 13.1 years and males at 15.6 years. Posterior densities were derived for each morphological stage, with complete fusion of the synchondrosis attained in all Queensland males over 16.3 years of age and females aged 13.8 years and older. The results demonstrate significant sexual dimorphism in synchondrosis fusion and are suggestive of intrapopulation variation between major geographic regions in Australia. This study contributes to the growing repository of contemporary anthropological standards calibrated for the Queensland milieu to improve the efficacy of the coronial process for medicolegal death investigation. As a stand‐alone age indicator, the basicranial synchondrosis may be consulted as an exclusion criterion when determining the age of majority that constitutes 17 years in Queensland forensic practice. Am J Phys Anthropol 157:42–57, 2015. © 2014 Wiley Periodicals, Inc.